The United States and China in Africa: What does the data say? - Janet Eom; Jyhjong Hwang; Lucas Atkins; Yunnan Chen; Siqi Zhou (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2017)
This brief examines how Chinese engagement compares to US engagement in African countries. How do oil exports influence Chinese and US trade relations with Africa? Why do Chinese and US firms favor investment in different African industries? What are the main sectors to which China and the United States provide loans in Africa? To answer such questions, this policy brief analyzes CARI's data on Chinese and US trade, foreign direct investment (FDI), and loans to Africa over the past 15 years. The authors find that Chinese engagement emphasizes Africa's infrastructure needs, key countries are consistently top destinations for different types of economic activities, and fluctuating commodity prices are important to both the United States and China in Africa.
Keywords: 330